A cross-sectional study of job satisfaction and leadership styles among the nurses in Aminu Kano teaching hospital - Ugwa, Emmanuel (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background/Objectives: Job satisfaction is the positive emotional state that results from the appraisal of one’s job or job experience. Lack of good leadership in healthcare is responsible for employee dissatisfaction and turnover. This study was undertaken to assess the levels of job satisfaction and its association with leadership styles among the nurses in Aminu Kano Teaching Hospital (AKTH); and to compare the levels of job satisfaction between senior and junior nurses. Context/Setting: This study was done at AKTH, Kano, Nigeria. Materials and Methods: This was a cross-sectional study. Ethical clearance and informed consent were obtained. A total of 350 participants responded on a 5-point Likert scale to questions related to their work experiences. The data was analysed using Statistical Package for the Social Sciences (SPSS version 16.0) software. Absolute numbers and simple percentages were used to describe categorical variables. Similarly, quantitative variables were described using the summarizing indices as appropriate. Statistical significance of differences between means was determined using analysis of variance. Significant associations between the measured variables were tested using Chi-square test for qualitative variable and Pearson’s coefficient of correlation for quantitative variables. Statistical significance was considered atP< 0.05. Result: The mean ages were 30.26 ± 4.76 and 40.19 ± 5.61 years for junior and senior nurses, respectively. Most of the junior and senior nurses were satisfied with their jobs (87.5% and 92.3% respectively); but the senior nurses were more satisfied compared with their juniors (P= 0.031). Democratic leadership styles showed significant association with job satisfaction. Conclusion: There are high levels of job satisfaction among nurses in AKTH and this is associated with leadership styles.